The Implementation of Herringbone Technique in Reading Comprehension at Second Semester of Non-English Department - Hidayatur Rohmah (Soegijapranata Catholic University, 2018)
Herringbone technique is the technique to help students find important information and main idea in a text by seeking the answer of six comprehension questions on a diagram. This study is intended to know how the lecturer’s implement herringbone technique to the students’ reading comprehension, especially detail information and main idea. The research was done at STAI Bahrul ‘Ulum Tambakberas. The subject of the study was the second semester of PAI-A students consisting 33 students. The study is descriptive qualitative conducted in four meetings. The researcher applied several techniques including observation, field notes, interview, questionnaire, and students’ test. To analyze the lecture’s implementation, data condensation which are selecting, focusing, simplifying, abstracting and transforming all the data found. Then data display means compressed the information, and the last was conclusion drawing. In analyzing the test, the researcher used holistic scoring scale adapted from Brown. And diagram used to analyze the students’ respond toward the implementation. The research finding shows that the implementation of herringbone technique is conducted into three phases; (1) pre-reading phase, which focussed on background knowledge and brainstorm, (2) whilst-reading, which consist on reading activity, fill and discuss the diagram, and (3) post-reading which mean to check the students’ understanding. In conclusion, the use of herringbone technique in teaching reading comprehension requires the lecture to do specific activities of teaching and learning process in accordance with the stages of herringbone technique. The student’s responses result to the herringbone questions and the number of main ideas during teaching learning process increased from first until fourth meeting. The students’ responded toward the implementation of herringbone technique was very good, gave possitive effect and helped them more easily in understanding the text.